AnaSP: A software suite for automatic image analysis of multicellular spheroids. Issue 1 (April 2015) - Piccinini, Filippo
Highlights We present a new software suite to analyze brightfield images of spheroids. AnaSP estimates several morphological parameters in a very limited time. We proved the high accuracy of the segmentation method proposed. Both AnaSP source code and a standalone executable version are freely available. The GUI developed makes AnaSP effective even without expertise in computer vision.